Mast Cell and VEGF Profile in Canine Soft Tissue Tumors - Ipek, V; Kaplan, O (Journal of the Hellenic Veterinary Medical Society, 2023)
Canine soft tissue sarcomas are a complex group that is difficult to treat with high invasion and metastasis characteristics. These tumors are divided into a wide variety of subtypes, but due to their general mesenchymal characteristics and morphological similarities, they are under a single group called soft tissue tumors together with benign ones. Tumor microenvironment including mast cells promotes tumor angiogenesis, proliferation, invasion, and metastasis, as well as mediating the mechanism of therapeutic resistance. In this study, the presence and relationships of mast cells with VEGF in benign and malignant soft tissue tumors were evaluated. As a result, mast cells showed a significant increase in malignant tumors compared to benign ones. In the VEGF analyzes performed for interpreting of angiogenesis, the immunostaining scores were also higher in malignant tumors. To the authors' knowledge, there is no previous study investigating mast cells and angiogenesis in canine soft tissue tumors. This study revealed that mast cell and VEGF scores are higher in malignant tumors compared to benign ones and can be considered as a prognostic marker. However, any correlation between mast cells and VEGF immune expressions could not be detected.